What can a free man worship? / Bertrand Russell - Russell, Bertrand (1872-1970) (Little blue book ; 677)
A free man?s worship / Bertrand Russell -- How I became a freethinker / John F. Mackey -- A comforting religion / M.M. Mangasarian -- The search for salvation / Marshall J. Gauvin